2021
DOI: 10.3389/fmolb.2021.747493
|View full text |Cite
|
Sign up to set email alerts
|

GSTP1 and GSTM3 Variant Alleles Affect Susceptibility and Severity of COVID-19

Abstract: Based on the premise that oxidative stress plays an important role in severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection, we speculated that variations in the antioxidant activities of different members of the glutathione S-transferase family of enzymes might modulate individual susceptibility towards development of clinical manifestations in COVID-19. The distribution of polymorphisms in cytosolic glutathione S-transferases GSTA1, GSTM1, GSTM3, GSTP1 (rs1695 and rs1138272), and GSTT1 were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Herein, we further substantiated results by haplotype analysis of GSTP1 genotypes and found that carriers of H2 haplotype (presence of GSTP1 rs1695 variant allele and GSTP1 rs1138272 referent allele) exhibited the lowest risk of susceptibility of COVID-19. In view of the fact that GSTP1 is highly expressed in lung tissue and might even be considered as predominant GST in the lungs, this result is biologically plausible [ 11 , 35–38 ]. As previously discussed, GSTP1 might modulate the susceptibility to various pulmonary diseases [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Herein, we further substantiated results by haplotype analysis of GSTP1 genotypes and found that carriers of H2 haplotype (presence of GSTP1 rs1695 variant allele and GSTP1 rs1138272 referent allele) exhibited the lowest risk of susceptibility of COVID-19. In view of the fact that GSTP1 is highly expressed in lung tissue and might even be considered as predominant GST in the lungs, this result is biologically plausible [ 11 , 35–38 ]. As previously discussed, GSTP1 might modulate the susceptibility to various pulmonary diseases [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the fact that GSTP1 is highly expressed in lung tissue and might even be considered as predominant GST in the lungs, this result is biologically plausible [ 11 , 35–38 ]. As previously discussed, GSTP1 might modulate the susceptibility to various pulmonary diseases [ 11 ]. The question arrases why examined polymorphisms of immediate and first line antioxidant enzymes SOD2, GPX1, and GPX3 in our study did not have association either with susceptibility or severity of COVID-19, despite the fact that redox homeostasis misbalance is one of the significant underlying mechanisms in COVID-19 disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering diverse variations in severity, duration and outcomes of coronavirus disease 2019 (COVID-19), defining a genetic predisposition, along with clinical and environmental factors, might be an important step in improving the diagnosis and treatment of high-risk individuals. Due to the established role of oxidative distress in the pathophysiology of COVID-19, it has been proposed that inter-individual differences in patients' clinical manifestations might also be affected by variations in genes encoding detoxifying and antioxidant enzymes, glutathione transferases (GSTs) (1). GSTs are a superfamily of enzymes that catalyze the conjugation of glutathione (GSH) to a wide range of chemical carcinogens, drugs and oxidative stress products.…”
Section: Introductionmentioning
confidence: 99%